The Existence of Equilibrium in Discontinuous Economic Games, I: Theory - Dasgupta, Partha; Maskin, Eric (Review of Economic Studies, 1986)
Partha Dasgupta, Eric Maskin; The Existence of Equilibrium in Discontinuous Economic Games, I: Theory, The Review of Economic Studies, Volume 53, Issue 1, 1 Jan